1970
DOI: 10.4314/acsj.v29i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics and genetic diversity of Ethiopian sesame genotypes

Abstract: Sesame (Sesamum indicum L.) is produced worldwide, although more than 96% of the world sesame seed is produced in Africa and Asia. The objective of this study was to determine morphological properties and identify the genetic diversity of cultivated sesame genotypes grown in different parts of Ethiopia. Three hundred sesame genotypes collected from diverse ecologies of Ethiopia and introduced from different African and Asian countries, were used in this study. Genotypes showed wide variability for most morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Four components with Eigen values greater than 1 aaccounted for 85.72% of the total variation present among the accessions (Table 3). This report is in agreement with the findings of Shim et al (2016) but contrary to the report of Tesfaye et al (2021) who retrieved 5 PCs which comprised 75.4% of the overall variation in 30 sesame genotypes. Many of the characters in the present study took their origin from the first two components.…”
Section: Resultssupporting
confidence: 91%
“…Four components with Eigen values greater than 1 aaccounted for 85.72% of the total variation present among the accessions (Table 3). This report is in agreement with the findings of Shim et al (2016) but contrary to the report of Tesfaye et al (2021) who retrieved 5 PCs which comprised 75.4% of the overall variation in 30 sesame genotypes. Many of the characters in the present study took their origin from the first two components.…”
Section: Resultssupporting
confidence: 91%
“…For instance; Shammoro et al . (2020) and Tesfaye et al . (2021) reported highly significant differences among genotypes for days to 50% flowering, number of primary branches per plant, number of pods per plant, seed yield, thousand seed weight, and days to 75% maturity among 100 genotypes and 300 genotypes, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…In Ethiopia, the application of AMMI and site regression model GGE models for explaining and analyzing the performance of genotypes and the tested environments have been very frequent among plant breeder in recent years. Various studies have been conducted in Ethiopia to analyze the effects of GEI on soybean genotypes (Gurmu et al, 2009;Asfaw et al, 2009;Adane et al, 2018), but only a few studies use the GGE biplot model. The studies on BLUP models and that of its graphics WAASB index has not been reported so far.…”
Section: Core Ideasmentioning
confidence: 99%
“…According to Tesfaye et al (2018), with its diverse environmental and climatic conditions, Ethiopia is endowed with a very large area of land, where soybean can be suitably produced. The land suitability analysis shows that soybean is the second among legumes in terms of land area that is moderately and highly suitable for its production in the country, with an estimated 42,067,700 (37.2%) hectares of land (Nigussie, 2018).…”
Section: Introductionmentioning
confidence: 99%